INTRODUCTION TO ENTOMOLOGY PART 1: THE EXTERNAL STRUCTURE OF INSECTS - Bragina, T.M. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
The textbook is devoted to the most diverse and numerous group of the animal world - insects.It provides theoretical data and practical recommendations for the study of the first part of the entomology course - the external structure of insects, tasks for testing and consolidating the knowledge gained. The textbook is intended for the assimilation of material on the discipline and improve the efficiency of independent work of students. There is also a glossary and dictionary of technical terms and names of animals and certain taxa. The textbook intended for students and teachers of universities and, other educational organizations.